Determination of Safe Benzene Concentration at Ciputat Gas Station - Cut Suci Almadiana1, Abdul Rohim Tualeka1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Benzene is a simple cyclic organic compounds whose concentrations are found usually low dilikungan. Benzene is often used in the industrial world, both home industry and the oil and gas industry. Benzene can enter into the body through the lungs, it can be through inhalation, gastrointestinal tract, and through the skin, If someone exposed to benzene at high concentrations, the levels of benzene into the lungs roughly half of the levels of benzene is absorbed, so that the incoming kealiran blood.This research is descriptive. The population in this study is a gas station worker Ciputat region totaling 10 people. The results of the study then analyzed quantitatively to determine the concentration secure benzene for workers obtained from the data concentration of benzene in the workplace, height workers, the weight of workers, heavy mice, respiration rate workers, time spent working, the surface area of the worker’s body surface area the body of laboratory mice, the highest dose of the toxin no effects in animal experiments (NOAEL), Km factors in animals (animal Km), Km factors in workers (Human Km), and the safe limit for workers toxin dose (SHD).The results of measurement of the concentration of benzene in petrol stations in the region Ciputat is 0,58mg / m3 (0.18 ppm), which means it is still below the Threshold Limit Value (TLV) according Permenakertrans 13 / MEN / X / 2011, the year 2011 is equal to 0, 5 ppm. In contrast to the NAB which have been set at 0.18 ppm, based on manual calculations for safe concentration limit of benzene obtained value of 0.02 ppm.